Fe3+ and Ce3+ modified nano-TiO2 for degradation of exhaust gas in tunnels - Luo Yin (De Gruyter, 2021)
To solve the environmental pollution caused by automobile exhaust in a tunnel, this study has developed a modified nano-TiO2 based on Fe3+ and Ce3+. The modified nano-TiO2 is prepared by the sol–gel method, and the modification adopts Fe3+ single-doping, Ce3+ sing-doping, and co-doping. The properties were also characterized by X-ray diffraction analysis, UV-vis diffuse reflectance analysis, fluorescence spectroscopy analysis, specific surface area analysis, and paramagnetic resonance popper analysis. The analyses showed that the doping of ions would change the energy band structure of nano-TiO2 and produce crystal defects, thus improving the photocatalytic activity. Then, a self-fabricated exhaust gas degradation device was used to carry out the exhaust gas degradation experiments. The results showed that the modification improves the catalytic efficiency of nano-TiO2, and Fe3+, Ce3+ co-doping > Ce3+ single-doping > Fe3+ single-doping > pure TiO2. At the dosage of 0.5%, the maximum degradation efficiencies of NO and CO before compensation are 53.85% and 16.39%, respectively, and the maximum degradation rates are 1.04 and 0.93 ppm·min−1. After compensation, the maximum degradation efficiencies of NO and CO are 20.14% and 6.04%, respectively. The maximum degradation rate is 0.40 and 0.41 ppm·min−1, respectively.